Faktor- faktor yang mempengaruhi lama rawat pada pasien pasca bedah Coronary Artery Bypass Graft (CABG) - Nur Rochayati; Pudji Lestari; Sri Handayani (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: Monitoring length of stay (LOS) while in the ICCU after CABG and examining risk factors can be a guiding initiative in improving services. Long LOS will not only lead to high costs and utilization but will also worsen outcomes for patients and their families. The length of stay in the ICCU room is an important indicator of the quality of critical care in patients undergoing CABG surgery.Purpose: To determine the factors that affect the length of stay of postoperative Coronary Artery Bypass Graft (CABG) patients in the ICCU ward of RSUP Dr. Kariadi Semarang.Method: Quantitative with a retrospective descriptive research design. The study sample was 69 post-CABG patients who were treated in the ICCU.Results: This shows that the factors that affect the length of stay of post-CABG patients in the ICCU are the length of time using POAF mechanical ventilation, the incidence of AKI, and pneumonia (with a p value <0.05).Conclusion: Post-operative factors such as prolonged use of mechanical ventilation, post-operative atrial fibrillation (POAF), pneumonia, and acute kidney injury (AKI) have an influence on the length of stay in post-CABG patients in the ICCU while preoperative factors (age, sex, comorbidities, LVEF), intraoperative factors (CPB duration, duration of anesthesia, number of grafts and aortic clamping time) and postoperative (potassium values, creatinine values, POCD, pericardial effusion, pleural effusion, and pulmonary edema) did not affect the length of postoperative patient care. CABG in the ICCU room.Keywords: Patient; Length of hospitalization; Coronary Artery Bypass Graft (CABG).Pendahuluan: Monitoring lama rawat (Length of Stay/ LOS) selama di ruang ICCU setelah tindakan CABG dan pemeriksaan terhadap faktor risiko dapat menjadi inisiatif panduan dalam peningkatan pelayanan. LOS yang panjang tidak hanya akan menyebabkan biaya dan utilisasi yang tinggi tetapi juga akan memperburuk outcome bagi pasien dan keluarga. Lama rawat di ruang ICCU merupakan indikator penting terhadap kualitas pelayanan kritis pada pasien yang menjalani operasi CABG.Tujuan: Untuk mengetahui faktor-faktor yang mempengaruhi lama rawat pasien pasca bedah Coronary Artery Bypass Graft (CABG) di ruang ICCU RSUP Dr. Kariadi Semarang.Metode: Kuantitatif dengan desain penelitian deskriptif retrospectif. Sampel penelitian sebanyak 69 pasien pasca CABG yang dirawat di ruang ICCU.Hasil: Menunjukkan bahwa faktor yang mempengaruhi lama rawat pasien pasca CABG di ruang ICCU adalah lama pemakaian ventilasi mekanik POAF, kejadian AKI, dan pneumoni (dengan p value <0.05).Simpulan: Faktor post operatif seperti lama pemakaian ventilasi mekanik, kejadian post operatif atrial fibrilasi (POAF), pneumoni dan kejadian Acute Kidney Injury (AKI) memiliki pengaruh terhadap lama rawat pada pasien pasca CABG di ruang ICCU sedangkan faktor pre operatif (usia, jenis kelamin, komorbid, LVEF), faktor intra operatif (lama CPB, lama anestesi, jumlah graft dan lama aorta klem) dan post operatif (nilai kalium, nilai kreatinin, POCD, efusi pericard, efusi pleura, dan edema pulmonary) tidak berpengaruh terhadap lama rawat pasien pasca CABG di ruang ICCU.